PROBLEMATIKA PENOLAKAN PASIEN DAN KELUARGA PASIEN TERHADAP PEMERIKSAAN CORONA VIRUS DISEASE-19 (COVID-19) MELALUI 3T (TEST, TRACE, TREATMENT) - Muhammad Rizal Ardiana; Siti Mariyam (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
The COVID-19 situation is a global pandemic which has caused a Public Health Emergency because its spread has almost reached all provinces in Indonesia. The number of cases and even the number of deaths is increasing, so that the Government of Indonesia is implementing countermeasures in accordance with statutory provisions, by carrying out Corona Virus Disease-19 (Covid-19) examinations through 3T (Test, Trace, Treatment)” for patients and their families. The formulation of the problems in this study are (1) What are the Problems of Refusing Patients and Patient Families to Examine Corona Virus Disease-19 (Covid-19) Through 3T (Test, Trace, Treatment)? (2) What are the obstacles and solutions to the problem of patient and family refusal to examine Corona Virus Disease-19 (Covid-19) through 3T (Test, Trace, Treatment)? The research method used in this research is empirical juridical. Data comes from primary data and secondary data. Primary data were collected by interviews and secondary data from literature studies, which were analyzed using qualitative analysis. The results of this study (1) Patients have the right to refuse any action that will be taken by medical personnel but in the current epidemic conditions this right does not apply this is in accordance with Law Number 36 of 2009 concerning Health (2) There are various obstacles in the Problems of Refusing Patients and Patient Families to Examine Corona Virus Disease-19 (Covid-19) Through 3T (Test, Trace, Treatment), namely the lack of technology in tracing patients where usually only interviews are carried out, the implementation of testing takes quite a long time is also an obstacle